Trends in the Development of Tailored Elastin-Like Recombinamer–Based Porous Biomaterials for Soft and Hard Tissue Applications - Mbundi, Lubinda; González-Pérez, Miguel; González-Pérez, Fernando; Juanes-Gusano, Diana; Rodríguez-Cabello, José Carlos (Frontiers in Materials, 2021)
Porous biomaterials are of significant interest in a variety of biomedical applications as they enable the diffusion of nutrients and gases as well as the removal of metabolic waste from the implants. Pores also provide 3D spaces for cell compartmentalisation and the development of complex structures such as vasculature and the extracellular matrix. Given the variation in the extracellular matrix composition across and within different tissues, it is necessary to tailor the physicochemical characteristics of biomaterials and or surfaces thereof for optimal bespoke applications. In this regard, different synthetic and natural polymers have seen increased usage in the development of biomaterials and surface coatings, among them, elastin-like polypeptides and their recombinant derivatives have received increased advocacy. The modular assembly of these molecules, which can be controlled at a molecular level, presents a flexible platform for the endowment of bespoke biomaterials properties. In this review, various elastin-like recombinamer based porous biomaterials for both soft and hard tissue applications are discussed, and their current and future applications evaluated.